Fashioning flax: Industry, region, and work in North American fibre and linseed oil, 1850-1930 - MacFadyen, Joshua D. (University of Guelph, 2009)
More flax was grown on the temperate grasslands of the Americas than in all the linen producing countries of Europe, and by the 1850s most of the crop was used to make paint. Flax has become a symbol of pioneer self sufficiency, but in British North America its main story begins on established Canadian farms in the mid nineteenth century and ends with an extensive Prairie flax belt. This thesis is about the industrial and intellectual fashioning of flax and flax products, and the adaptability of producers to new markets and environments. It finds that flax in North America was not about homespun and self-sufficiency but about industrial production driven by demand for intermediate fibre products and the emerging oilseed sector. By the nineteenth century, North American flax appeared in vehicles and houses more than clothing and bedding. Flax fibre was usually for manufacturing upholstery, cordage, and rough textiles such as sails and grain bags, and flax seed produced linseed oil, the foundation for paint, varnish, and linoleum. In both its forms, flax demonstrates how commodities disappeared into a world of manufactured goods, and how spurious images develop over time. The romantic story of independent yeomen bringing flax from field to fabric is presented at most pioneer museums, but the real picture would include complex intermediate goods in carriages, homes, and furniture; family and First Nations work gangs harvesting flax owned by millers, not farmers; and Mennonites and other sodbusters bringing extensive flax cultivation to new land through market and contract prices set by large integrated enterprise. The process of painting was connected to the process of farming, and in Canada consuming colour meant cultivating the plains. The plant grew quickly on new breaking and best on land that was free of disease, and therefore it became a significant first crop on some of the most fragile and unforgiving northern grasslands. Over two centuries of flax fibre promotion by state and farm officials have had little ...